Severity Assessment of Patients Having Community-Acquired Pneumonia by Using CURB-65 Scoring System. - Khalid Farouq Yousef, Sufian Khalid.M. Noor, Mohamed Osman Elamin, Hatim. M. Badri, Waheeb.D. Alharbi, Abdullah Muhammad Alzhrani, Wahaj.A. Khan, Halah Tarig Albar, Amir El-Mubarek Ali, Ahmed.A.Osman (The International Journal of Multiphysics, 2024)
Globally, pneumonia is the most common infectious cause of death, and the second leading cause of life years lost. The CURB-65 score helps in classifying patients having community-acquired pneumonia (CAP) according to the mortality risk and their management. We aimed to assess the severity of patients having CAP by using CURB 65 scoring system. This was a prospective observational, hospital-based study included 102 patients with CAP admitted to Atbara teaching hospital, Sudan. We collected sociodemographic data, co morbidities, presenting symptoms, clinical, laboratory and imaging findings and followed the patients till reach their outcomes. Most of participants were males 62 (60.8%) and belonged to age group more than 55 years in 57 (59.9%). Hypertension (HTN) and diabetes mellites (DM) were the most common co-morbidities 23 (22.5%) and 19 (18.6%) respectively. Seventeen patients (16.7%) were managed as outpatients and had CURB score 0-1. Whereas, 70 (68.6%) of them managed at medicine wards and 15 (14.7%) of them were admitted to intensive care unit (ICU). Regarding patients’ outcomes, 14 (13.7%) of participants died in which 1 (2.9%) of low-risk group, 3 (10%) of intermediate risk group and 10 (27%) of high-risk group. Conclusion: CURB 65 scoring system is a quick and easy tool and it could be effective categorizing system used in a crowded emergency departments to identify the low-risk patients who could benefit from outpatient management.